Thermal Performance Analysis of Affordable House in the Equatorial Coastal Area of the Tropics - Puteri Fitriaty; Iwan Setiawan Basri; Andi Jiba Rifai Bassaleng; Nur Rahmanina Burhany; Zubair Butudoka (Pusat Publikasi Nusantara, 2024)
Affordable housing subsidised by the government in Indonesia often poses many problems, including an uncomfortable internal environment that leads to the massive use of mechanical ventilation. Designing an affordable house undoubtedly faces challenges due to the very small building lots, while it should provide many spatial needs and functions for the occupants’ daily activities. Because of limited funding provided by the government, affordable house design is often based only on basic needs, thus scarcely considering thermal comfort for the occupants. This study evaluates the thermal performance of affordable houses built for the 2018 great earthquake, tsunami, and liquefaction victims in Palu’s coastal area. Field measurements were conducted in an affordable housing complex, and a sample house was selected, representing a raised floor house design prototype. External and internal climate conditions were recorded for nine days to establish the hourly thermal trend. Hobo Onset H21 microclimate stations were used to record external climate conditions, whereas Onset Hobo U12-012 T-RH-Light was employed to record internal thermal conditions. The result showed that the thermal condition in the sample house was intolerably hot. The main cause of these conditions is the design of the roof and building envelope. The selected materials with a high U-value also worsen the thermal conditions in the sample house